A Note on Rice Production, Consumption and Import Data in Indonesia - Rosner, L. Peter; McCulloch, Neil (2012)
Debate about Indonesian rice policy has focused on estimates of production and consumption levels, and the level of imports they imply. However, Indonesian rice production and consumption data are controversial. Rice consumption as estimated from household survey data is much lower than officially reported rice production. This suggests that Indonesia is a net rice exporter, but in fact it has generally been a net importer. Some researchers argue that rice consumption data are underestimated; others contend that production is over-estimated because of inaccuracies in 'eye estimates' of harvested area. This paper reviews how rice production and consumption are measured, notes major weaknesses, and surveys attempts to reconcile consumption and production data and examine their consistency with rice import data. It concludes that rice prices are the only accurate indicator of the balance between supply and demand, and hence of the appropriate level of imports.